Hard Living Kids - Tosco, Davide; Arvat, Massimo (Italy, 2000)
On the southern tip of Africa the American dream is alive and unwell. Behind Cape Town's Table Mountain, over 100 street gangs fight bloody turf wars for control of protection rackets, prostitution and drugs. Deriving dress and behavior from images in U.S. movies and television shows, they have dubbed themselves Young Americans and Ugly Americans, L.A. Boys, Cool Boys, Dixie Boys and Laughing Boys, Art Loving Kids and the Hard Living Kids (HLK), Asbestos Kids, New Yorkers and The A-Team. The biggest gang is the Young Americans. Smaller but better organized are the HLK. The film follows the story of Schoolboy and Richie Gee, two young ex-HLK gangsters whom the filmmakers met in prison in 1997 while running workshops for incarcerated juveniles. Now, after more than two years these young men are trying to adjust to the stigmatization that exists within the communities to which they have returned. Following their stories, the film explores the dynamics and life style of gang members inside and outside prison, describing their life in the ghettos and townships, how they grew up in poverty and joined teenaged gangs for survival.
Soros Documentary Fund
Soros Documentary Fund
Keywords: Documentary films